How to subtract monomials with different exponents? How do you subtract monomials with different exponents?

Example of subtracting monomials with different exponents.

Subtract the following monomials with different exponents

34f^{3} - 4f^{2}f

Solution.

34f^{3} - 4f^{2}f =

34f^{3} - 4f^{2}f^{1} =

34f^{3} - 4f^{2 + 1} =

34f^{3} - 4f^{3} = 30f^{3}

34f

34f

34f

Answer: 30f^{3}.

Example of subtracting monomials with different exponents.

Subtract the following monomials with different exponents

31h^{2} - 6hh

Solution.

31h^{2} - 6hh =

31h^{2} - 6h^{1}h^{1} =

31h^{2} - 6h^{1 + 1} =

31h^{2} - 6h^{2} = 25h^{2}

31h

31h

31h

Answer: 25h^{2}.

Example of subtracting monomials with different exponents.

Subtract the following monomials with different exponents

47nn - n^{2}

Solution.

47nn - n^{2} =

47n^{1}n^{1} - n^{2} =

47n^{1 + 1} - n^{2} =

47n^{2} - n^{2} = 46n^{2}

47n

47n

47n

Answer: 46n^{2}.

Example of subtracting monomials with different exponents.

Subtract the following monomials with different exponents

20y^{4} - 5y^{4} - z^{4}

Solution.

20y^{4} - 5y^{4} - z^{4} =

(20y^{4} - 5y^{4}) - z^{4} =

15y^{4} - z^{4}

(20y

15y

Answer: 15y^{4} - z^{4}.

Note, we can only subtract like terms (monomials) and we cannot subtract unlike terms (monomials).

See the subtracting unlike monomials.

See the subtracting like monomials.